DETERMINANTS OF BANK PROFITABILITY: THE CASE OF THE REGIONAL DEVELOPMENT BANK (BPD BANK) IN INDONESIA - Heyvon Herdhayinta; R.A. Supriyono (Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
Introduction: The Regional Development Bank (BPD Bank) is expected to be a strong, highly competitive bank, which will contribute to the growth and even distribution of sustainable regional economies. Background Problem: A review by the Financial Service Authority (OJK) of the BPD Bank’s business growth indicates the low competitiveness of the BPD Bank, relative to other commercial banks. Novelty: Limited prior studies have been conducted on the profitability determinants of the BPD Bank, especially in Indonesia, and previous studies have only focused on the internal determinants of profitability. Hence, this research aims to analyze both the internal and external profitability determinants of the BPD Bank in Indonesia. Research Method: This study analyzes 135 observations in total from all 27 BPD banks in Indonesia for five years, from 2011 to 2015. This research measured bank profitability using ROA and ROE as the dependent variables. The independent variables are the internal and external determinants of bank profitability. The internal determinants of profitability consist of TA, TCORCAP, CAR, NPL, LDR, OE/OI and NIM; whilst the external determinants include TMS, INF and BIRATE. Findings: The findings of this study show that the profitability of the BPD Bank, as measured by its Return on Assets (ROA) and Return on Equity (ROE), is significantly determined internally by the total assets, LDR, OE/OI, and NIM and externally by the BIRATE and inflation. Those variables have positive relationships with profitability, except for OE/OI and inflation, which have negative relationships with profitability. In addition, two hypotheses are only partially supported, in which the total core capital and CAR show negative relationships only with ROE. Conclusion: The findings of this paper provide a deeper insight to help manage the profitability of the BPD Bank, which eventually can promote sustainable economic development.